Emotions and Economic Shocks in a First-Price Auction - Ronald Bosman; Arno Riedl (Tinbergen Institute, 2003)
We investigate experimentally whether emotions affect bidding behavior in a firstprice auction. To induce emotions, we confront subjects after a first auction series with apositive or negative random economic shock. We then explore the relation between emotions andbidding behavior in a second auction series. Our main results are: (i) the economic shock has asubstantial impact on the experienced emotions of bidders; (ii) the emotional statesystematically influences bidding behavior. In particular, negative emotions induce morecompetitive bidding. Our findings show that for a good understanding of bidder behavior theemotions have to be taken into account.
Keywords: A12; C72; C91; C92; 330; auction; economic shock; emotion; experiment.; Auktion; Schock; Test; Theorie; Emotion